A Systematic Review of Fire Evacuation Modeling in Buildings and Defining the Framework of Safe Architecture Design for Egress - Atefeh Omidkhah; Mohammad Reza Bemanian; Mohammad Reza Hafezi (صفه)
Evacuation modelling is a tool for measuring the performance of building design for safe evacuation of occupants during emergencies such as fires. The first evacuation modelling efforts date back to the mid-70s. To date, a wide range of evacuation models have been developed, with numerous problems having been studied in various scientific disciplines. In the present study, a database of 152 original papers was developed through a systematic search in the field of evacuation modelling, and their data was used to answer three key questions. The first question was that of the role of architectural design in the entire body of research. Architectural design issues are one of the five fields in evacuation modelling research being considered in a variety of scales in the design process. The second question was that of important elements of evacuation modelling. This was answered by data analysis. From the perspective of variables and their relationship, it was found that several elements have been considered as independent variables in evacuation modelling, with their design features being considered as measures to explain other dependent parameters. The third question was that of the relationship between architectural elements and other modelling parameters. When a modelling is aimed at evaluation of a design, the results can cause significant changes in the original design.Modelling methods are also relevant to the levels of design development. In early stages, macroscopic modelling can lead to the rejection or acceptance of a design alternative or schema, or demonstrate whether or not the design conforms to the required performance criteria. In more advanced stages, microscopic modelling is applied as a tool to make fine tunings of dimensions, configuration details and layouts of columns and furniture. The results showed that the swarm intelligence-based methods are the emerging field among microscopic models that can result in lower computational cost and more accurate results.